Phytoremediation of Contaminated Soil and Water - Terry, Norman (CRC Press, 2009)
Phytoremediation is an exciting, new technology that utilizes metal-accumulating plants to rid soil of heavy metal and radionuclides. Hyperaccumulation plants are an appealing and economical alternative to current methods of soil recovery. Phytoremediation of Contaminated Soil and Water is the most thorough literary examination of the subject available today. The successful implementation of phytoremediation depends on identifying plant material that is well adapted to specific toxic sites. Gentle remediation is then applied in situ, or at the contamination site. No soil excavation or transport is necessary. This severely contains the potential risk of the pollutants entering the food chain. And it's cost effective. The progress of modern man has created many sites contaminated with heavy metals. The effected land is toxic to plants and animals , which creates considerable public interest in remediation. But the commonly used remedies are ex situ, which poses an expensive dilemma and an even greater threat. Phytoremediation offers the prospect of a cheaper and healthier way to deal with this problem. Read Phytoremediation of Contaminated Soil and Water to learn just how far this burgeoning technology has developed.